Investigation of Antioxidant Potential and Phytotoxic Effects of Ganoderma lucidum Methanol Extract - Fuat Bozok; Tülin Eker; Gökhan Sezer; Adnan Bozdoğan; Hasan Hüseyin Doğan; Saadet Büyükalaca (Turkish Journal of Agriculture: Food Science and Technology)
The aim of this study is to reveal allelopathic effects and antioxidant activities of methanolic extract of Ganoderma lucidum in Zorkun plateau (Osmaniye). It was determined that methanolic extract of G. lucidum has significantly phytotoxic effect by increasing the doses (1, 2, 4, 8 mg/mL) on Hordeum vulgare and Triticum aestivum. Total phenol and flavonoid amounts of G. lucidum were 114.55 mg/kg and 8.95 mg/kg, respectively. 2,2-diphenyl-1-picrylhydrazyl (DPPH), scavenging activity (60%, 91% and 92%), reducing power (0.83, 1.43 and 2.23 Abs), and nitric oxide (NO) scavenging activity (48%, 55% and 70%) of this mushroom at the different concentrations (1.25, 2.5 and 5 mg/mL) were determined, respectively. However, H2O2 scavenging activity of the different concentrations (0.0156-0.125 mg/mL) was found as 18%, 56%, 60% and 86%, respectively. Based on these findings, it can suggest that G. lucidum methanolic extract has significantly phytotoxic effect and antioxidant activity. The present study is the first report on the phytotoxic effects and antioxidant activities of G. lucidum which consumed and collected from Amanos Mountains.